Europeanisation and multi-level environmental governance in a post-conflict context: the gradual development of environmental impact assessment processes in Bosnia-Herzegovina. (October 2015) - Fagan, Adam; Sircar, Indraneel
The post-conflict case of Bosnia-Herzegovina provides a challenging case for the approaches employed by the European Union to bolster state and non-state actor capacities related to environmental governance in post-socialist states. This article examines four major consultative environmental impact assessment processes in Bosnia-Herzegovina in order to identify factors that either enable or impede the development of multi-level environmental governance at the state and sub-state entity levels. Larger environmental non-governmental organisations provide scientific opinions and smaller organisations lack capacity to participate at all. The complex configuration of state institutions, compounded by inadequate staffing and funding, creates impediments for effective governmental hierarchy during environmental impact assessments. However, international financial institutions and technical consultants involved in environmental impact assessments have taken a pivotal tutelage role to familiarise local stakeholders with best practice, which has led to some improvements in multi-level environmental governance during environmental impact assessments in Bosnia-Herzegovina, though the impact is dependent on staff retention in Bosnian public bodies.